Suicide Precipitants Differ Across the Lifespan but Are Not Significant in Predicting Medically Severe Attempts - Choo, Carol C. (Int J Environ Res Public Health, 2018)
An important risk factor for suicide assessment is the suicide precipitant. This study explores suicide attempt precipitants across the lifespan. Three years of medical records related to suicide attempters who were admitted to the emergency department of a large teaching hospital in Singapore were subjected to analysis. These cases were divided into three age groups: Adolescence, Early Adulthood, and Middle Adulthood. A total of 540 cases were examined (70.9% females; 63.7% Chinese, 13.7% Malays, 15.9% Indians), whose ages ranged from 12 to 62. There were eight cases above the age of 65 years which were excluded from the analysis. Significant differences were found in precipitants for suicide attempts across the lifespan. Middle adults had relatively fewer relationship problems, and adolescents had comparatively fewer financial and medical problems. The models to predict medically severe attempts across the age groups using suicide precipitants were not significant. The findings were discussed in regards to implications in suicide assessment and primary prevention in Singapore, as well as limitations and recommendations for future research.